Considerations of Microstructural Influences for Diffusion Welding of Metals in Microsystem Technology. Issue 8 (12th April 2013) - Gietzelt, Thomas; Toth, Volker; Lambach, Heinz; Dittmeyer, Roland
Abstract Diffusion welding is a special high‐tech solid joining technique. Most research was done and publications were written in the years between 1970 and 1980. The aim of this paper is to take a closer look at the fundamental processes inside the material during diffusion welding and to discuss the relation between the materials microstructure for diffusion processes from a material science point of view. For this, it is necessary to discuss the impact of different lattice defects and to observe the intrinsic energetically conditions of a metal originating from its delivery state and manufacturing history, as well as its surface condition. In particular, emphasis is paid to the special requirements for joining of micro process devices.